Reverse Engineering in Strength and Conditioning: Applications to Agility Training. Issue 4 (22nd August 2022) - Turner, Anthony N.; Read, Paul; Maestroni, Luca; Chavda, Shyam; Yao, Xiang; Papadopoulos, Kostas; Virgile, Adam; Spiegelhalter, Abbie; Bishop, Chris
ABSTRACT: Typically, a coach may follow a process in which they first identify the key performance indicators of their sport, determine the physical attributes that map back to them, and then distribute the development of those capacities over the allocated timeframe. Furthermore, effective training plans are based on a theoretical or biological basis for how we move and adapt to exercise stimuli, coupled with an understanding of how these are best sequenced, such that one stimulus and subsequent adaptation can potentiate the next. Thus, reverse or backward engineering, when appropriately converged with the plans of those devised around nutrition, conditioning, technical, and tactical training, for example, likely gives athletes the best chance of attaining their performance goals. The aim of this article is to describe the application of reverse engineering, exampling it within the context of developing an athlete who can demonstrate a high level of agility.